Examining the connection between position-based power and social status across 70 cultures - Wasiel, Arkadiusz; Górski, Maciej R; Bond, Michael Harris; Yeung, Victoria Wai Lan; Akaliyski, Plamen; Akello, Grace; Park, Joonha; Joshanloo, Mohsen; Sokolov, Boris; Hussain, M Azhar; Li, Liman Man Wai; Olechowski, Mateusz; et al. (British journal of social psychology, 2025)
Even in the most egalitarian societies, hierarchies of power and status shape social life. However, power and received status are not synonymous-individuals in positions of power may or may not be accorded the respect corresponding to their role. Using a cooperatively collected dataset from 18,096 participants across 70 cultures, we investigate, through a survey-based correlational design, when perceived position-based power (operationalized as influence and control) of various powerholders is associated with their elevated social status (operationalized as perceived respect and instrumental social value). We document that the positive link between power and status characterizes most cultural regions, except for WEIRD (Western, Educated, Industrialized, Rich, Democratic) and Post-Soviet regions. The strength of this association depends on individual and cultural factors. First, the perceived other-orientation of powerholders amplifies the positive link between perceived power and status. The perceived self-orientation of powerholders weakens this relationship. Second, among cultures characterized by low Self-Expression versus Harmony (e.g., South Korea, Taiwan), high Embeddedness (e.g., Senegal), and high Cultural Tightness (e.g., Malaysia), the association between power and status tends to be particularly strong. The results underline the importance of both individual perceptions and societal values in how position-based power relates to social status.
Keywords: dospělí; sociální hodnoty; Female; Social Class; srovnání kultur; Adult; mladý dospělý; ženské pohlaví; moc (psychologie); lidé; Social Values; Power, Psychological; Male; Young Adult; Cross-Cultural Comparison; společenská třída; lidé středního věku; mužské pohlaví; Middle Aged; Humans